Macronutrients and performance - Williams, C. (Journal of Sports Sciences, 1995)
Athletes should eat a well-balanced diet made up of a wide variety of foods in sufficient quantity to cover their daily energy expenditures. Carbohydrate-containing foods should provide approximately 60-70% of their daily energy intake, protein approximately 12-15%, with the remainder being provided by fat. The higher carbohydrate intakes, however, are only recommended during preparation for, and immediate recovery from, heavy training and competition. Adopting nutritional strategies to increase muscle and liver glycogen stores before, during and after exercise can improve performance. The protein requirements of most athletes are fulfilled when their daily intake is between 1.2 and 1.7 g per kg body mass. This amount of protein is provided by a diet which covers the athlete's daily energy expenditure. Although fat metabolism contributes to energy production during exercise, and the amount increases with endurance training, there is no evidence to suggest that athletes should increase their fat intake as a means of improving their performance.